Kosmicflush: Terminal year-end report - Altarejos, Danica U. (Animo Repository, 2022)
Founded in the middle of the Covid-19 Pandemic in 2021, the company aims to challenge existing barriers in the cosmetics industry that prevent a lot of people from being able to express themselves through beauty products and fully be who they want to be. With the goal of creating an inclusive, vegan, and cruelty-free cosmetic product that is competitively priced, The founders were able to materialize such ideals with Kosmicflush which not only gave confidence to its customers regardless of their ethnicities but also became an avenue of empowerment and innovation wherein women can feel confidently beautiful whenever and wherever.